Strategy to Strengthening Forest Farming for Sustainable Mangrove Forest Management in the Coastal Area, Deli Serdang, Indonesia - Christofel Limbong; Samsuri; Alfan Gunawan Ahmad (Talenta Publisher, 2023)
Mangrove forests can be used directly or indirectly by communities/farmer groups around the coast. However, with the rampant forest destruction that occurs, the community or farmer groups need to be equipped with capacity building about the importance of the mangrove ecosystem and its impact on their livelihood. This study aims to identify the condition of mangrove forests in the research area and determine strategies for institutional development of forest farmer groups in coastal areas at the Production Forest Management Unit. The research method used is a qualitative method with interviews; while the analytical method used is the SWOT analysis. Based on the results of the analysis of the Internal Factor Analysis Summary (IFAS) with a strength factor value of 0.054 and a weakness value of 0.47. From the calculation of the internal environment score (IFAS) value, namely the strength factor minus the weakness factor, the value of x was obtained as the horizontal axis 0.054-0.047 = 0.007. Based on the External Factor Analysis Summary (EFAS) analysis results, the opportunity factor had a value of 0.054 with threats having a value of 0.047. The results showed that the external calculation score (EFAS), namely the opportunity factor (opportunities) reduced by the threat factor, obtained the Y value as the vertical. The identification of internal (IFAS) and external (EFAS) factors indicated that the position of institutional development of forest farmer groups in coastal areas was in quadrant one (I) or in an aggressive position that supports the SO development strategy (aggressive development strategy)